Pengenalan Sistem Pertanian Pintar untuk Kader-Kader Pemberdayaan Kesejahteraan Keluarga - Kiki Prawiroredjo; Engelin Shintadewi Julian; Muhammad Doris; Sentot Novianto (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
The activities of the Family Welfare Empowerment cadres in Cideng Village in growing vegetables and fruits have been carried out routinely and manually so that it requires considerable energy and time. The smart farming system is one solution in meeting the community's food needs that can be done independently and automatically. In order to participate in increasing public knowledge, the Electrical Engineering and Mechanical Engineering Study Program, Faculty of Industrial Technology, Trisakti University in the 2024-2025 academic year has implemented a Community Service program in Cideng Village, Central Jakarta to introduce knowledge about smart farming systems that use digital technology that can improve the quality and quantity of sustainable agricultural yields. Participants who took part in the extension were cadres of the Family Welfare Empowerment Driving Team. The method used was counceling. The result of this community service activity was an increase in knowledge about smart farming systems from 50% to 76% based on questionnaires distributed before and after the extension. This program needs to be continued to be implemented with mentoring from lecturers and students as a sustainable community service program.